The development and application of an educational technology acceptance model - Lopez, Dobrila (Curtin University, 2013)
This research developed and implemented the educational technology acceptance model ETAM. The model was developed to investigate the attitude towards technology acceptance in educational settings. It is evolutionary in its nature and combines the two well‐known instruments, the Technology Acceptance Model (TAM) and the What Is Happening In this Classroom (WIHIC) to make a new educational technology acceptance model. This model incorporated all the WIHIC scales (Student Cohesiveness, Teacher Support, Involvement, Investigation, Task Orientation, Cooperation and Equity) and two TAM scales (Perceived Usefulness and Perceived Ease of Use). It also includes four demographic elements: Age, Gender, Prior Experience and English as a first language.To gather lecturer perceptions, semi‐structured interviews were carried out with the lecturers teaching the courses. The semi‐structured interviews were analysed qualitatively and thematic analysis was used. To gather student perceptions, a purpose‐written questionnaire was developed. The student perspective was analysed quantitatively. A total of 208 student responses were collected. The analysis involved formal statistical testing of a number of hypotheses.To determine the unique contributions of each component, path analysis and multiple regressions were used. The major findings were that all the WIHIC constructs have a positive correlation with Perceived Usefulness and Perceived Ease of Use. The unique contributions of each of the WIHIC constructs in the ETAM model were identified. The two major contributors were: Task Orientation and Studying. Task Orientation explained 15% of the variance in the Perceived Usefulness and 11% of the variance in Perceived Ease of Use. This is a significant and a unique contribution of this study to identify that Task Orientation and Studying are major predictors in technology acceptance. This finding informs practitioners and allows them to use a shorter version of the questionnaire while still capturing the main influences of technology acceptance in the classroom.The main result of this study was a new model for technology acceptance the Educational Technology Acceptance Model (ETAM) designed for educational environments. The results of this study add to the body of knowledge of technology acceptance model (TAM) applications in educational settings. The study also adds new knowledge to the better understanding of educational environment constructs. The results of the study could benefit students by collecting information that helps them to make decisions on the future use of the software tool, and informs course designers in tertiary institutions about the usefulness of the technology and students’ attitudes towards technology acceptance. The results helps other practitioners make informed decisions on whether to offer the tool to students and how to get the best use from the tool, if used. The study adds to the body of knowledge around the interaction between technology and the classroom environment. It adds to the body of knowledge by gaining a better understanding of attitudes toward software acceptance in an educational setting.